Seismic Capacity of Reinforced Concrete Eccentric Braced Frame (EBF) With Vertical Link Using 20% GGBFS - I Gde Eka Wiranatha; Wijaya, Ming Narto; Susanti, Lilya (Rekayasa Sipil, 2024)
EBF-V bracing is highly attractive due to its good seismic performance in high seismic zones. Vertical link beams as a component are capable of high elastic displacement and ductility to absorb lateral forces through shear-bending collapse mechanisms. However, the lateral load capacity of the bracing has to be sacrificed as it tends to decrease. The present study focuses on the capacity and lateral behavior of reinforced concrete eccentrically braced frame (EBF) with vertical link beam and tighter reinforcement spacing in the link beam in combination with GGBFS. GGBFS at 20% can improve the mechanical properties by reducing the pore number of the concrete due to the smaller particle size of OPC.This study uses CBF-V as a control to investigate the seismic behavior of tightly spaced transverse reinforcement (75 mm) in EBFs’s vertical link beam with eccentricities of 15 cm and 25 cm. In addition, the role of GGBFS was also observed through the displacement and ductility of the frame. As a result, the CBF has the highest plasticity. However, the tight reinforcement spacing of the vertical link beam in the EBF-V-15 results in the highest restraint, resulting in excellent stiffness and ductility through earthquake absorption with a shear collapse mechanism. In addition, GGBFS also plays a role in improving the collapse mechanism, which is characterized by large elastic displacement and high ductility.